2020
DOI: 10.1155/2020/4638192
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of the Liver in Nanomedicine as an Actor in the Elimination of Nanostructures or a Therapeutic Target

Abstract: e development of nanostructures for therapeutic purpose is rapidly growing, following the results obtained in vivo in animal models and in the clinical trials. Unfortunately, the potential therapeutic efficacy is not completely exploited, yet. is is mainly due to the fast clearance of the nanostructures in the body. Nanoparticles and the liver have a unique interaction because the liver represents one of the major barriers for drug delivery. is interaction becomes even more relevant and complex when the drug d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 155 publications
0
26
0
Order By: Relevance
“…Thus, in the present study our attention focused on hepatotoxicity for two main reasons: on the one hand it is well-known that Dox can cause liver toxicity (Bagchi et al1995); furthermore, it has been shown that this organ, being one of the main filters of the human body, can capture the exogenous nanoparticles in the circulation, leading to toxicity (Zhang et al 2016). Reasons for liver accumulation of NPs may include the sheer size of the liver (Bartneck et al 2014), its highly fenestrated endothelium (Abdel-Misih and Bloomston 2010), as well as the high number of Kupffer cells, the resident macrophages in the liver (Baboci et al 2020, Kretzschmar 1996.…”
mentioning
confidence: 99%
“…Thus, in the present study our attention focused on hepatotoxicity for two main reasons: on the one hand it is well-known that Dox can cause liver toxicity (Bagchi et al1995); furthermore, it has been shown that this organ, being one of the main filters of the human body, can capture the exogenous nanoparticles in the circulation, leading to toxicity (Zhang et al 2016). Reasons for liver accumulation of NPs may include the sheer size of the liver (Bartneck et al 2014), its highly fenestrated endothelium (Abdel-Misih and Bloomston 2010), as well as the high number of Kupffer cells, the resident macrophages in the liver (Baboci et al 2020, Kretzschmar 1996.…”
mentioning
confidence: 99%
“…Plasma levels of synthetic miRNA antagonists or miRNA mimics distribute broadly after intravenous administration but later accumulate mostly in the liver and kidney and remain high up to 24 h after injection [ 118 ]. On the other hand, NPs biodistribution studies have demonstrated that the majority of injected nanomaterials usually accumulate in the liver before undergoing hepatic clearance [ 119 ]. This makes liver cancer a good model for testing miRNA-based therapy approaches as this organ can be easily targeted with different delivery systems.…”
Section: Application Of Mirna-based Therapeutics In Selected Cancersmentioning
confidence: 99%
“…In addition to the particle size, the properties of the particle surface, such as its electronegativity, hydrophobicity, and surface tension, also affect the distribution of drugs. For example, particles with a negative surface charge are easily taken up by the liver, while particles with a positive surface charge are easily taken up by the lungs [99].…”
Section: Passive Targetingmentioning
confidence: 99%